University students’ career adaptability as a mediator between cognitive emotion regulation and career decision-making self-efficacy - Lee, Ahram; Jung, Eunju (Frontiers in Psychology, 2022)
As modern society experiences rapid changes, the unpredictability of the labor market is increasing. College students preparing to join the world of work may experience increased anxiety and stress related to their uncertain career trajectory. Regulating such negative emotions and adjusting to the changing circumstances may influence their career development. Thus, the current study aimed to investigate the relationship between cognitive emotion regulation (CER), specifically adaptive CER and maladaptive CER, and career decision-making self-efficacy (CDMSE), with career adaptability (CA) as a mediating factor. The path analysis model consisting of adaptive CER, maladaptive CER, CA, and CDMSE was tested with 361 Korean college juniors and seniors who were facing school-to-work transition. The results of the study were as follows. First, adaptive CER had a positive relation with CA and CDMSE, while maladaptive CER had a significant negative relation only with CA. Second, CA and CDMSE were positively related. Third, both adaptive CER and maladaptive CER had a significant indirect effect on CDMSE via CA. Based on these results, theoretical and practical implications are proposed, and the limitations of the study are discussed.